2020
DOI: 10.21873/anticanres.14137
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Metabolomic Changes in Mice With Time-restricted Feeding-attenuated Spontaneous Metastasis of Lewis Lung Carcinoma

Abstract: Background/Aim: Time-restricted feeding (TRF) during the dark phase of the day restores metabolic homeostasis in mice. Materials and Methods: We performed untargeted metabolomic analysis on plasma from mice subjected to TRF that attenuates high-fat diet-enhanced spontaneous metastasis of Lewis lung carcinoma (LLC). Results: Twenty-four of 152 identified metabolites differed among the four dietary groups (non-LLC-bearing mice fed the AIN93G diet and LLC-bearing mice fed the AIN93G, the highfat diet (HFD), or TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Although data are limited to a few animal studies, TRF intervention has been shown to have an antineoplastic effect in various cancers [ 15 17 , 20 ]. Animal or population evidences of TRF effect on lung cancer are however arising from only two experiments [ 19 , 43 ]. Both studies have found that 12-h TRF abrogated the obesity-enhanced spontaneous metastasis of Lewis lung cancer, as well as restored the health phenotypic impairment or shifted the plasma metabolic profiles changes driven by high-fat diet [ 19 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although data are limited to a few animal studies, TRF intervention has been shown to have an antineoplastic effect in various cancers [ 15 17 , 20 ]. Animal or population evidences of TRF effect on lung cancer are however arising from only two experiments [ 19 , 43 ]. Both studies have found that 12-h TRF abrogated the obesity-enhanced spontaneous metastasis of Lewis lung cancer, as well as restored the health phenotypic impairment or shifted the plasma metabolic profiles changes driven by high-fat diet [ 19 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal or population evidences of TRF effect on lung cancer are however arising from only two experiments [ 19 , 43 ]. Both studies have found that 12-h TRF abrogated the obesity-enhanced spontaneous metastasis of Lewis lung cancer, as well as restored the health phenotypic impairment or shifted the plasma metabolic profiles changes driven by high-fat diet [ 19 , 43 ]. Although the above studies have both demonstrated the potential inhibitory effects of 12-h TRF on lung cancer metastasis within the context of high-fat diet-induced obesity, the impact of TRF on lung cancer growth and progression in nonobese animals remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…3-Hydroxybutyric acid is a main ketone body generated from excessive acetyl-CoA production resulting from hepatic β-oxidation; it is an indicator of excessive lipid oxidation and potential mitochondrial dysfunction (45,46). Previous studies have shown that TRF elevates 3-hydroxybutyric acid in plasma (47,48). Decrements of this ketone body in mammary tumors by TRF suggest an increase in utilization of this energy source by the tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…They also observed that TRF decreased the phosphorylation of AKT (also known as PKB, protein kinase B) in tumor tissues, supporting the idea that TRF may be related to autophagy. Yan et al [49–51] also demonstrated that TRF could attenuate the spontaneous metastasis of Lewis lung cancer and reduce the expression of oncogenic genes through a series of animal experiments.…”
Section: Potential Antitumor Effects Of Trementioning
confidence: 99%